Uso de realidad virtual inmersiva en el control de ansiedad situacional en pacientes con diagnóstico hematooncologico (2024)
Introduction: In patients in hematoncology services situational anxiety is generated due to the requirement of invasive procedures, notification of alarming diagnoses and long hospital stays, in this scenario, the use of IVR arises as a tool that mitigates these effects; IVR decreases the levels of situational anxiety, generating changes in the neurophysiological activity of brain areas related to emotions. Objective: To develop a research plan to stratify the use of immersive virtual reality as a coadjuvant strategy in the reduction of discomfort related to clinical scenarios in the adult population hospitalized at the Santa Fe Foundation in Bogota. Research plan: From the literature search on IVR, it was possible to define the context of the topic of study in order to delimit the research problem and aspects involved (software) to finally choose the immersive technology for research. Results: The importance of interventions such as immersive virtual reality in the management of situational anxiety is highlighted. This conceptual support strengthened the validity and rationale of the work, demonstrating a deep understanding of the topic and providing a solid foundation for future research and clinical practice. Conclusion :The implementation of IVR contributes to improving health care and generating an impact on the management of situational anxiety in invasive procedures such as in the case of the peripheral central catheter (PICC) in the hemato-oncology service of the Fundación Santa Fe de Bogotá.